Timor-Leste Economic Report : Investing in the Next Generation - World Bank (Washington, DC: World Bank, 2022)
Buffeted by COVID-19 and Tropical Cyclone Seroja, the non-oil economy grew by 1.5 percent in 2021. A record-high budget with expenditure of nearly 90 percent of GDP bolstered government consumption. A series of fiscal and quasi-fiscal stimulus measures supported employment and incomes, thereby allowing households to maintain their consumption. On the demand side, gross capital formation shrunk while net exports expanded. The oil economy grew by 8.3 percent, bringing the total economic growth to 4.4 percent.1 The government lifted the pandemic-related state of emergency at the end of November 2021, but challenges remain. Following a relatively brisk start, the vaccination campaign has moved sluggishly in recentmonths. Nevertheless, the authorities have initiated vaccination of children and adolescents between 12 and 18 years old, while booster shots have been made available. There has been a concerning surge of Dengue Fever with 5,000 reported cases (and 54 fatalities) to date since January 2022‒a more than seven-fold increase from the same period a year ago. All restrictions for inbound international vaccinated travelers to Timor-Leste havebeen rescinded. By the end of May 2022, the partly vaccinated and fully vaccinated figures in Timor-Leste stood at 85.4 percent and 73.4 percent, respectively.